Mesoporous Bioglasses Enriched with Bioactive Agents for Bone Repair, with a Special Highlight of María Vallet-Regí's Contribution - Antonio J. Salinas; Pedro Esbrit (MDPI AG, 2022)
Throughout her impressive scientific career, Prof. María Vallet-Regí opened various research lines aimed at designing new bioceramics, including mesoporous bioactive glasses for bone tissue engineering applications. These bioactive glasses can be considered a spin-off of silica mesoporous materials because they are designed with a similar technical approach. Mesoporous glasses in addition to SiO2 contain significant amounts of other oxides, particularly CaO and P2O5 and therefore, they exhibit quite different properties and clinical applications than mesoporous silica compounds. Both materials exhibit ordered mesoporous structures with a very narrow pore size distribution that are achieved by using surfactants during their synthesis. The characteristics of mesoporous glasses made them suitable to be enriched with various osteogenic agents, namely inorganic ions and biopeptides as well as mesenchymal cells. In the present review, we summarize the evolution of mesoporous bioactive glasses research for bone repair, with a special highlight on the impact of Prof. María Vallet-Regí´s contribution to the field.